H3K4me3 Histone ChIP-Seq Analysis Reveals Molecular Mechanisms Responsible for Neutrophil Dysfunction in HIV-Infected Individuals - Piatek, Paweł; Tarkowski, Maciej; Namiecinska, Magdalena; Riva, Agostino; Wieczorek, Marek; Michlewska, Sylwia; Dulska, Justyna; Domowicz, Małgorzata; Kulińska-Michalska, Małgorzata; Lewkowicz, Natalia; Lewkowicz, Przemysław (Frontiers in Immunology, 2021)
Peripheral neutrophils in HIV-infected individuals are characterized by impairment of chemotaxis, phagocytosis, bactericidal activity, and oxidative burst ability regardless of whether patients are receiving antiretroviral therapy or not. Neutrophil dysfunction leads not only to increased susceptibility to opportunistic infections but also to tissue damage through the release of reactive oxygen species (ROS), proteases, and other potentially harmful effector molecules contributing to AIDS progression. In this study, we demonstrated high levels of histone H3 lysine K4 trimethylated (H3K4me3) and dysregulation of DNA transcription in circulating neutrophils of HIV-infected subjects. This dysregulation was accompanied by a deficient response of neutrophils to LPS, impaired cytokine/chemokine/growth factor synthesis, and increased apoptosis. Chromatin immunoprecipitation sequencing (ChIPseq) H3K4me3 histone analysis revealed that the most spectacular abnormalities were observed in the exons, introns, and promoter-TSS regions. Bioinformatic analysis of Gene Ontology, including biological processes, molecular function, and cellular components, demonstrated that the main changes were related to the genes responsible for cell activation, cytokine production, adhesive molecule expression, histone remodeling via upregulation of methyltransferase process, and downregulation of NF-κB transcription factor in canonical pathways. Abnormalities within H3K4me3 implicated LPS-mediated NF-κB canonical activation pathway that was a result of low amounts of κB DNA sites within histone H3K4me3, low NF-κB (p65 RelA) and TLR4 mRNA expression, and reduced free NF-κB (p65 RelA) accumulation in the nucleus. Genome-wide survey of H3K4me3 provided evidence that chromatin modifications lead to an impairment within the canonical NF-κB cell activation pathway causing the neutrophil dysfunction observed in HIV-infected individuals.